Repairing damaged nets - Mumbai Archive Project Team (Jio Institute, 2024)
Repairing damaged nets, instead of replacing them with new ones, is necessary because of their high cost. A high-quality fishing net carries a substantial price tag, often up to one lakh rupees. These nets have a lifespan of approximately six months to one year.